Marx and Contemporary Critical Theory: The Philosophy of Real Abstraction - Oliva, Antonio; Oliva, Angel; Novara, Iván (Marx, Engels, and Marxisms, 2020)
1. Introduction -- Part I: Reconstructing the Problem of Real Abstraction -- 2. Value Form and Abstract Labour in Marx: A Critical Review of Alfred Sohn-Rethel's Notion of 'Real Abstraction' -- 3. Money as a Practical Abstraction: From Feuerbach to Marx Through Hess (1841–1844) -- 4. Real Abstraction: Philological Issues -- 5. Marx's Method and the Use of Abstraction -- 6. Method and Value: Engels Through Sohn-Rothel -- 7. Marx: The Method of Political Economy as an Ontological Critique -- 8. Marx, Berkeley, and Bad Abstractions -- 9. On Capital as Real Abstraction -- 10. The Lost Roads and the Steep Paths of 'Real Abstraction' -- 11. On Real Objects That Are Not Sensuous: Marx and abstraction in actu -- 12. The Concept of Form in the Critique of Political Economy -- 13. The Real Contradictions (Commodities as Coherence of Contradiction) -- 14. Reification and Real Abstraction in Marx's Critique of Political Economy -- 15. The Critique of Real Abstraction: From the Critical Theory of Society to the Critique of Political Economy and Back Again -- 16. Real Abstraction in Light of the 'Practical Revolution in Epistemology' (Labriola). Considerations on the Uses and Limits of a Concept -- 17. Real Abstraction in the History of the Natural Sciences -- 18. Zapatista Autonomy: The Invention of Time as a Discontinuity and Untotaling Category.